Times virtuais globais em multinacionais de países em desenvolvimento : um estudo de caso no Brasil - Weinberg, Manfred (Universidade do Vale do Rio dos Sinos, 2018)
Global virtual teams have specific characteristics in relation to face-to-face teams and the work dynamics and interpersonal relationships are more complex in a virtual team, and it is necessary to manage differently. This is largely due to the fact that the global virtual team components have communication technology impacts (not face to face) and a lot of electronic interaction as integration possibility. In addition, there are barriers in the work process such as: cultural differences; time zone; language, which considerably increases the challenges in relation to face-to-face teams. The present dissertation looked for to investigate and analyze the key factors in a global virtual team management under the multinational in a developing country focus. The method used was the single case study, because it was contemporary with limited data accessibility, when the researcher has limited access to other sources (GIL, 2002). For data analysis was used the triangulation data and content technique. The result shows key factors for virtual team’s good management, corroborating with other research on this subject. However, this study allowed us to observe peculiarities such as specific factors in a developing country multinational that were not verified in the literature.
Keywords: Times virtuais globais; Compartilhamento de conhecimento; Diversidade cultural; Comunicação; Tarefas interdependentes; Gerenciamento de conflitos; Global virtual teams; Knowledge sharing; Cultural diversity; Communication; Interdependent tasks; Conflict management; ACCNPQ::Ciências Sociais Aplicadas::Administração